Screening of two glucocorticoids in non-prescription skin whitening creams purchased via internet in Iraq by HPLC method - Mohanad Naji Sahib (Journal of Applied Pharmaceutical Science, 2018)
Using illegal lightening creams or preparations were reported widely throughout the world. Therefore, the present study aimed to the simultaneous determination of clobetasol 17-propionate (CB) and betamethasone 17-valerate (BM) in skin whitening creams purchased via internet from Iraqi market. The liquid chromatography was performed with Zorbax Eclipse Plus C18 (150 × 3.0 mm ID, 5 μm), mobile phase acetonitrile (70): water (30), the flow rate of 1 ml/ min and a UV detector at 240 nm. The method was validated in terms of linearity, selectivity, precision, accuracy, limit of detection and quantification and stability of working solutions. The analytical method proved to be linear in the range of 1-40 μg/ml for both CB and BM. The limits of detection and quantification for CB and BM were (0.024 μg/ml, 0.075 μg/ml) and (0.035 μg/ml, 0.107 μg/ml), respectively, which revealed the sensitivity of the method. The precision, accuracy and stability study of working solutions of the method were between 0.52 to 1.93%, 97.87 to 100.55% and 0.48 to 1.72%, respectively. The results revealed that all purchased samples from beauty/cosmetic shops contained different levels of CB and/or BM. Moreover, the mixed preparations which purchased from the pharmacies also contained either CB or BM. The present study offers simple and sensitive analytical method to be used in the quality control laboratories and forensic point of view to identify illegal or counterfeit medicinal products or cosmetic preparations. Moreover, a new and restrict regulations must be implemented to ban the use of topical corticosteroids without prescription.
Keywords: Betamethasone, Clobetasol, HPLC, validation, whitening cream.